2021
DOI: 10.3390/antiox10081187
|View full text |Cite
|
Sign up to set email alerts
|

Variation of the Polyphenolic Composition and Antioxidant Capacity of Freshly Prepared Pomegranate Leaf Infusions over One-Day Storage

Abstract: In recent decades, an intensive search for natural and novel types of antioxidant polyphenolics has been carried out on numerous plant materials. However, the current literature has very little information on their storage stability in the form of freshly prepared infusions. This study aims to characterize the polyphenolic composition and the antioxidant capacity of pomegranate (Punica granatum L.) leaf infusions over one-day storage (analyzed at 0, 2, 4, 6, 8, and 24 h). Spectrophotometric evaluation demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Three different spectrophotometric methods were used to characterize the antioxidant capacity of the extracts: ABTS and DPPH radical scavenging methods and FRAP (ferric reducing antioxidant power). The DPPH- and ABTS-based determinations were performed as described by Lemos et al [ 24 ], and FRAP was carried out as reported by Yu et al [ 25 ]. Similar to what was performed in the quantification of the different phenolic classes, the three antioxidant assays were carried out on a microscale using 96-well microplates (PrimeSurface MS- 9096MZ, Frilabo, Maia, Portugal) and microplate readers (Multiskan GO Microplate Photometer, Thermo Fisher Scientific, Vantaa, Finland).…”
Section: Methodsmentioning
confidence: 99%
“…Three different spectrophotometric methods were used to characterize the antioxidant capacity of the extracts: ABTS and DPPH radical scavenging methods and FRAP (ferric reducing antioxidant power). The DPPH- and ABTS-based determinations were performed as described by Lemos et al [ 24 ], and FRAP was carried out as reported by Yu et al [ 25 ]. Similar to what was performed in the quantification of the different phenolic classes, the three antioxidant assays were carried out on a microscale using 96-well microplates (PrimeSurface MS- 9096MZ, Frilabo, Maia, Portugal) and microplate readers (Multiskan GO Microplate Photometer, Thermo Fisher Scientific, Vantaa, Finland).…”
Section: Methodsmentioning
confidence: 99%
“…The antioxidant activity of sample extracts was determined using 2,2 -azino-bis(3ethylbenzothiazoline-6-sulfonic acid) (ABTS), 2,2-di(4-tert-octylphenyl)-1-picrylhydrazyl (DPPH), and ferric-reducing antioxidant power (FRAP) spectrophotometric methods, as reported by Yu et al [27], with some modifications.…”
Section: Determination Of Antiradical and Antioxidant Capacitiesmentioning
confidence: 99%
“…The study by Lamiae et al, 2021 reported that pomegranate peel extract was 283.86 mg GAE/g dw and 185.37 mg QE/g dw polyphenols and flavonoids respectively, while aril extract of pomegranate was polyphenols and flavonoids 166.90 mg GAE/g dw and 57.43 mg QE/g dw respectively. The studies showed that leaves infusion of pomegranate reported that tannins, flavonoids and total phenols contents were 24.20 mg EC/g DW, 55.84 mg RU/g DW and 133.47 mg/g Gallic acid equivalent respectively (Yu et al, 2021). Peels and seeds of pomegranate extracts were higher in total phenolics (0.16-0.73 mg GAE/mg extract) from conventional extraction, while higher contents of total flavonoids (0.019-0.068 mg CATE/mg extract) obtained from sonication-assisted extraction (Campos et al, 2022).…”
Section: Phenols Flavonoids and Tanninsmentioning
confidence: 99%
“…Its ointment or paste is applied as a treatment for skin injuries and arthritis. The infusion or decoction has been utilized to care for stomach disorders, urinary tract infection, and to treat sore throat and renal colic (Yu et al, 2021). Current research on products of Punica granatum has considerably augmented and profitably drained customers' concentration to medicinal and nutritional values, growing the pomegranate industry's expansion globally.…”
Section: Introductionmentioning
confidence: 99%